KONSEP WAKAF SAHAM - Roifah, Tri Nadirotur (Finance : Journal of Accounting and Finance, 2024)
Abstract Waqf is an Islamic economic instrument related to the Islamic socio-economic system. Waqf is synonymous with land and buildings, but today there are several new types of waqf, such as books, agricultural machinery, daily necessities, stocks, and even cash waqf and share waqf. Share waqf is one model of developing productive waqf, meaning that the waqf can later be used for community businesses. Stock wakaf can also be considered an extension of existing wakaf, such as cash wakaf. Stock wakaf is an effort to concretise the form of productive wakaf in society. There are three important criteria to consider when managing stock wakaf investments: First, the wakaf capital must not be reduced; therefore, capital protection must be the top priority. Second, the investments made must be able to generate stable and consistent income to be distributed to the beneficiaries of the endowment so that the endowment can be sustainable and reap endless rewards from Allah. Third, all investments made for the endowment must be in accordance with Sharia law.